A transferência da execução penal para o país do condenado - Hermes Vilchez Guerrero (2017)
The present work studies the transference of the criminal execution, especially the foreign prisoners transfer to the country where he maintains juridical, sociological, affective and political ties, as a form of effectuate the purpose of the conviction and because of the higher goal to humanize the fulfillment of the sentence. To do so, the internationalization of criminal law is examined, with special emphasis on international criminal cooperation, especially in the context of globalization. In the same way, the process of permanent humanization through which Criminal Law is passed and the Criminal Policy Principles that guide the elaboration of laws, the judicial process, and especially the sentencing procedure and those governing the execution of criminal sentences. The transfer of the criminal execution to the convicted persons country of origin is of particular importance as a result of the intense migratory flow, the large number of Brazilian prisoners abroad, as well as the high rate of foreign prisoners serving their sentence in Brazil. Therefore, research is done on these phenomena, which although not directly related to Criminal Law, are of interest to the study of the institute under examination. The analysis is carried out taking as assumptions the constitutional principles and programmatic documents, national and international, concerning the person of the condemned person. The present institute is studied and defended with reference to the purpose of criminal execution: social reintegration. This objective alone justifies its application. In this work, the emergence and evolution of the prisoners transfer is examined, being the first treaties reported. Finally, an analytical study of the institute is carried out, examining each of its constituent elements and the treatment given to each of them in the bi-national treaties signed by Brazil and in the existing multilateral treaties in the world. This is absolutely necessary because only with the proper knowledge of the institute, its proper standardization and prediction, as proposed in this work, the transfer of the criminal execution to the convicted persons country of origin may become concrete and effective, that is, an institute which humanizes the penaltys enforcement and fulfills its purpose.